Unconventional satellite resistance peaks in moiré superlattice of h-BN/ AB-stacked tetralayer-graphene heterostructures - Fumiya Mukai; Kota Horii; Ryoya Ebisuoka; Kenji Watanabe; Takashi Taniguchi; Ryuta Yagi (Communications Physics, 2021)
The superposition of two layers of graphene or hBN at an angle gives rise to interesting geometrical structures, named Moiré superlattice, that has been intensively studied recently. The authors report on experimental data and simulations for twisted h-BN/AB-stacked tetralayer graphene heterostructures, finding that band gaps appear because of Fermi surface nesting due to the specific angle used.